INHIBITION OF SESAME SEEDLING GROWTH BY XANTHOMONAS CAMPESTRIS PV. SESAMI CULTURE SECRETIONS - I. Rehman; F. Deeba; M. I. ul Haque; S. M. Saqlan Naqvi (Journal of Animal and Plant Sciences, 2013)
Xanthomonas campestris pv. sesami (Xcs) is rod shaped, gram negative bacterium. This bacterial pathogen causes the bacterial blight of sesame and significantly reduces its yield. Severely infected leaves defoliate and spots are formed on the twigs. Present study was conducted to check the effect of culture filtrate of Xcs on germination and seedling of sesame. Different concentrations of culture filtrates of Xcs in MS (Murashige and Skoog) medium were used to monitor its effect on seed germination, height and root length of sesame seedlings. It was observed that Xcs greatly affects the length of root and length of whole seedling and slows down the process of germination. Smallest root and seedling height was obtained with 4% culture filtrate while there was normal growth in control sesame seedlings.
Keywords: Sesame; Xanthomonas campestris; culture filtrate; seedling